Billy Graham Evangelist to the World - Pollock, John (San Francisco Harper & Row, 1979)
Covers the personal life and evangelistic career of Billy Graham from 1970 to 1979.
Keywords: Graham, Billy, -- 1918-2018. Graham, Billy, -- 1918-2018 Graham, Billy, -- 1918-